The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.26552/ems.2021.2.87-98
|View full text |Cite
|
Sign up to set email alerts
|

Value-Based Management: A Case Study of Visegrad Four Countries

Abstract: Research background: As companies evolve over time, so do their goals. In the past, the main goals of companies were profit and goals (as market share), are no longer relevant or effective. These goals are outdated, and companies have replaced them with goals that are consistent with the current changing times of competition. Worldwide, most large companies are using, or planning to use, a new approach called value-based management that focuses on value creation. Therefore, the main goal of companies using a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Further challenges include raising adequate capital to continue operations, lack of financial means to purchase needed material, increased cost of procuring needed materials for operations, and inadequate access to loans and credit facilities (Tijani et al, 2021). In short, companies' ability to create value was heavily impaired (Mitan, Siekelova, Rusu, Rovnak, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Further challenges include raising adequate capital to continue operations, lack of financial means to purchase needed material, increased cost of procuring needed materials for operations, and inadequate access to loans and credit facilities (Tijani et al, 2021). In short, companies' ability to create value was heavily impaired (Mitan, Siekelova, Rusu, Rovnak, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the government should not only provide financial support but utilizes its public resources to provide a combined subsidy strategy to support enterprises’ long-term development. At last, regarding replication of this study in other countries, it is suspectable that the main conclusion will still hold worldwide but the exact mechanism of the CEO locality effect may differ across country samples ( Bulathsinhalage and Pathirawasam, 2017 ; Mitan et al, 2021 ; Valaskova et al, 2021a ). Other changes in the external conditions, such as emerging industries ( Kliestik et al, 2020 ; Durana et al, 2021b ; Lazaroiu et al, 2021 ; Valaskova et al, 2021c ), life cycles ( Durana et al, 2021a ), pandemic shocks ( Tijani et al, 2021 ), etc., may also strengthen or weaken the connection between local-province CEO identity and management myopia operations.…”
Section: Discussionmentioning
confidence: 82%
“…In general, the literature suggests that corporate governance has a positive effect on stock liquidity, specifically that corporate governance and stock liquidity have a significant and positive relationship. These studies suggest that superior corporate governance improves stock liquidity [see, for example, (Mangena and Tauringana, 2007;Chung et al, 2010;Tang and Wang, 2011;Prasanna and Menon, 2012;Mitan et al, 2021;Arazpour and Fadaeinejad, 2014)]. Sosnowski (2022) Studied the persistence firm's earning reports in the process of IPO, and they found that there is higher persistence in the pre-IPO earnings as compared to the year of IPO earnings.…”
Section: Corporate Governance Financial Transparency and Stock Liquiditymentioning
confidence: 99%